18F-Fluorodeoxyglucose Positron Emission Tomography Combined With CT in Unresolved ICU Infections: Diagnostic Yield and Clinical Consequences in a Retrospective Cohort - Knut Kampe; Theresa Lohse; Susanne Klutmann; Ivayla Apostolova; Gerold Soeffker; Lina Ko; Axel Nierhaus; Stefan Kluge (Critical Care Explorations, 2026)
IMPORTANCE: In critically ill patients with sepsis, the infectious focus may remain unclear despite microbiology, ultrasound, and conventional cross-sectional imaging. In this setting, 18 F-Fluorodeoxyglucose Positron Emission Tomography Combined With CT (FDG PET/CT) is used selectively, but its diagnostic value and downstream clinical consequences are not well defined. OBJECTIVES: To assess the diagnostic yield of FDG PET/CT in selected ICU patients with unresolved infection, describe the infectious foci detected, and document subsequent diagnostic and therapeutic actions. DESIGN, SETTING, AND PARTICIPANTS: Retrospective single-center cohort study of 108 FDG PET/CT scans performed in 103 adult patients with sepsis treated in the ICUs of a tertiary university hospital. PET/CT was requested either to search for an unknown infectious focus or to confirm or exclude a suspected infectious focus. MAIN OUTCOMES AND MEASURES: PET/CT findings suspicious for infection, confirmation according to a composite clinical reference standard, classification as clinically informative, diagnostic performance, and diagnostic or therapeutic actions after imaging. RESULTS: FDG PET/CT detected a subsequently confirmed infectious focus in 72 of 108 scans (66.7%). Eight additional findings suspicious for infection were not confirmed, and one scan was classified as false negative. Apparent sensitivity was 98.6% (95% CI, 96.0–100.0%), specificity 77.1% (95% CI, 63.2–91.1%), positive predictive value 90.0% (95% CI, 83.4–96.6%), and negative predictive value 96.4% (95% CI, 89.6–100.0%). When PET/CT was used to search for an unknown focus, at least one infectious site was subsequently confirmed in 53 of 81 scans (65.4%). When it was used to confirm or exclude a suspected focus, results were diagnostically conclusive in 24 of 27 scans (88.9%). Overall, 77 scans (71.3%) were considered clinically informative. Imaging findings were followed by additional noninvasive diagnostics in 50 scans, invasive diagnostic or therapeutic procedures in 52 scans, and antimicrobial modification in 44 scans. CONCLUSIONS AND RELEVANCE: In selected critically ill patients with sepsis and unresolved infection, FDG PET/CT often identified a confirmed infectious focus or helped reduce diagnostic uncertainty. These findings support its use as a complementary, problem-oriented diagnostic tool rather than as routine imaging in ICU sepsis. Because referral was selective, the study was retrospective, and the composite reference standard was imperfect, diagnostic performance estimates should be interpreted cautiously. Prospective studies are needed to define patient selection and determine whether PET/CT improves patient-centered outcomes.